Estudo comparativo do acúmulo de massa seca e macronutrientes por plantas de Zea mays e Ipomoea hederifolia - Carvalho, L.b. (2014)
Two experiments were carried out under greenhouse conditions to study the accumulation and distribution of dry mass and macronutrients in maize and Ipomoea hederifolia. Plants of both species had grown, separately, in pots with sand substrate and irrigation with nutrient solution. Treatments were represented by the times of evaluation, realized in intervals of 14 days, starting at 21 days after emergence (DAE). A maize plant showed slight growth up to 30 DAE, when dry mass allocation was higher in roots and leaves (80%); while an I. hederifolia plant, up to 50 DAE, when the allocation of dry mass was higher in offshoots and leaves (79). Dry mass accumulation was almost five times greater in maize (134 g per plant) than in I. hederifolia (29 g per plant). The average values of N and K contents were greater in I. hederifolia. Maximum accumulations of macronutrients by maize were 1,431; 474; 1,832; 594; 340, and 143 mg per plant, while by I. hederifolia, 727; 52; 810; 350; 148, and 65 mg per plant, for N, P, K, Ca, Mg, and S, respectively. Mean accumulation rate of dry mass and macronutrients by maize plants was crescent up to 87 DAE, reaching the maximum value at 103 DAE; while being crescent up to 121 DAE by I. hederifolia plants, reaching the maximum value at 138 DAE. Thus, beyond the interference on harvesting process, a population of I. hederifolia also can compete with maize crop for nutrients.